Effectiveness of Psychological Intervention by Videoconference for Family Members with Depression of Farmers Who Have Committed Suicide. Issue 6 (December 2020) - Nayak, Raghavendra B.; Bhatia, Triptish; Mahadevaiah, Mahesh; Bheemappa, A.
Background: In India two thirds of the population is directly or indirectly dependent on agriculture. The suicide rate for farmers throughout the world is higher than the non-farming population with India being no exception. Family members of the household where a member has committed suicide are at an increased risk for depression, anxiety and suicide. There is a paucity of trained counsellors in India, while there is sufficient research showing counselling and therapy through videoconferencing is just as effective as in-person therapy. It is however, not commonly practiced in India, especially in rural settings. We propose to evaluate psychiatric morbidity and assess feasibility and effectiveness of videoconferencing for family members of farmers who had committed suicide. Objectives: The objective is to evaluate family members of farmers who have committed suicide for psychiatric morbidity and psychosocial risk factors. We aim to identify depression, anxiety and suicidal risk in family members and then administer psychological intervention through video-conferencing for depression to study its effectiveness in the cohort. Methodology: The data on completed farmer suicide would be collected from district authorities and police departments. Home visit would be made by research staff to assess the risk factors for the farmers who completed suicide. Family members would be screened for anxiety and depression and severity of depression and suicidal ideas would be rated. The family members having mild to moderate depression would be randomised and CBT based psychological intervention (5 sessions) over three months would be given by trained psychologist through videoconferencing. The outcome would be measured at the end of six months. Conclusions: Psychological interventions through video-conference might be beneficial in the treatment of mild to moderate depression in family members of the farmers who have committed suicide.